Flotation Separation of Diaspore and Kaolinite by Using a Mixed Collector of Sodium Oleate-Tert Dodecyl Mercaptan - Man, Xiaofei; Ou, Leming; Wang, Chenliang; Jin, Saizhen; Ma, Xiqi (Frontiers in Chemistry, 2019)
Sodium oleate (NaOl), a collector in diaspore flotation, has been widely used for more than 30 years, while its low selectivity becomes an issue under today’s process requirement. This study introduced tert dodecyl mercaptan (TDM) together with NaOl as a mixed collector to improve selectivity in diaspore flotation. We found that using the mixed collector of NaOl/TDM (total concentration 0.1 mM, the molar ratio 8:2 of NaOl: TDM) at pH=9-10 significantly effectively separated diaspore and kaolinite. Comparing the recovery of Al2O3 and the ratio of Al2O3 to SiO2 (A/S) treated by NaOl/TDM (pH=9) and NaOl (pH=10), the Al2O3 recovery and A/S in concentrate for NaOl/TDM are 7.5% and 2.2 higher than that for NaOl in mixed mineral flotation. Also, surface tension measurements, Zeta potential measurements and Fourier Transform Infrared (FTIR) spectra analysis were used to examine its selectivity from a flotation mechanical perspective. Surface tension measurements show that mixed collector NaOl/TDM has stronger surface activity and hydrophobic association than NaOl. The results of Zeta potential measurements and FTIR spectra analysis indicate that NaOl and TDM can selectively co-adsorb diaspore through physical adsorption. Moreover, the adsorption of TDM promotes the adsorption of NaOl on diaspore. However, when NaOl/TDM treats on kaolinite together, TDM can hardly adsorb on mineral surface, nor can it promote the adsorption of NaOl.